The Evolution of the Theoretical Basis for Studying National Economic Security - Hrybinenko Olha M. (Problemi Ekonomiki, 2019)
The aim of the article is to study the cause-effect relationship between challenges of globalization and provision of national economic security under modern conditions. The evolution of the theoretical basis for studying national economic security is investigated. The analysis showed that scientific research and empirical studies in the field of the formation and provision of economic security have been carried out for a long time. Economic security issues were examined through determining the impact of international trade on the welfare of the nation, which is directly related not only to the state of military security but of economic security as well. Classical economists drew attention to tools to ensure stability of markets, coordination of interests of their participants. With the progress in international economic relations under the influence of increasing global challenges, the focus of research in the field of economic security is expanding from traditional issues to those related to environmental problems, organizational crime, terrorism, human security, etc. Among the new areas of security research, it is worth highlighting the development of the concepts of cooperative security, democratic world, unconventional security; the theory of transnational networks; social and economic catastrophe theory; the conflict theory; synergetics, etc. Studying the theoretical and methodological bases for determining economic security allows to define it as a system and as a process, which in turn requires appropriate identification of components in assessing economic security, namely from the point of view of the subject (human security, national security, international security); the object of security (military, political, economic, etc.); level of security (national, regional, global). It is concluded that, despite a fairly significant level of scientific achievements in studying the security concept, this category is still complex and contradictory and requires appropriate conceptualization through applying appropriate approaches to determining the content of economic security, which determines the further direction of research on national economic security under modern conditions.